Effectiveness of Force Feedback on Movement Time and Path for Target Selection in the Presence of Distractors. (September 2015) - O'Connor-Dreher, Ryan; Vu, Kim-Phuong L.; Marayong, Panadda; Strybel, Thomas Z.; Battiste, Vernol
Implementation of new, effective onboard computer technologies into commercial cockpits will alter the current role and actions taken by pilots. These new technologies will require precise and efficient input methods due to the unstable nature of a cockpit environment. The benefits of including haptic force feedback for input devices have been shown in previous research. The present study investigated the effects of force feedback distractors on movement time, movement path, and workload when force-enabled distractors were present. Results demonstrated that in the presence of distractors, resistive spring force levels most strongly influenced all performance measures. Attractive gravitational force levels had no impact on movement times and minimal impact on path of movement.